'A pinch of unseen, unguarded dust': The World and Self in Thomas Hardy's Poems. (March 2018) - Szuba, Monika
Abstract : The essay discusses selected poems from Thomas Hardy's vast body of poetry, focusing on representations of the self and the world. Employing Maurice Merleau-Ponty's concepts such as the body-subject, wild being, flesh, and reversibility, the essay offers an analysis of Hardy's poems in the light of phenomenological philosophy. It argues that far from demonstrating 'cosmic indifference', Hardy's poetry offers a sympathetic vision of interrelations governing the universe. The attunement with voices of the Earth foregrounded in the poems enables the self's entanglement in the flesh of the world, a chiasmatic intertwining of beings inserted between the leaves of the world. The relation of the self with the world is established through the act of perception, mainly visual and aural, when the body becomes intertwined with the world, thus resulting in a powerful welding. Such moments of vision are brief and elusive, which enhances a sense of transitoriness, and, yet, they are also timeless as the self becomes immersed in the experience. As time is a recurrent theme in Hardy's poetry, this essay discusses it in the context of dwelling, the provisionality of which is demonstrated in the prevalent sense of temporality, marked by seasons and birdsong, which underline the rhythms of the world.